Analisis Kemampuan Pemecahan Masalah Matematis Siswa Kelas VIII pada Materi SPLDV - Shafa Khadijah; Dadang Rahman Munandar (Universitas Batanghari Jambi, 2022)
The ability to solve problems is crucial to increase cognitive skills and can motivate students to learn mathematics. This research aims to determine the mathematical problem-solving ability of VIII graders in Academic year 2021/2022. The sample in this research is specifically class VIII/K students totaling 19 students. This type of research is carried out by qualitative descriptive research while data collection techniques used with giving test of ability problem solving as many as 3 questions. The results of the analysis in this research showed that the average of ability problem solving are 49,995% and belongs to moderate category. This research can be concluded that the average ability of students in SPLDV learning material is in the moderate category, especially in applying it to daily activities.